The Objectives, Roles, and Functions of Technical Guidance (TG) for Strengthening the Competence of Teachers of Computer-Based Written Examination Subjects - Sudiyo Widodo; Sri Budiyono; Pujo Darmo (Edunesia: Jurnal Ilmiah Pendidikan, 2022)
This study aims to explore the role, objectives, and functions of technical guidance for teachers in charge of written exams in preparation for entrance exams to state universities. This research activity was conducted in Sulawesi. Sampling was carried out at the Golden Tulip Essential Makassar Hotel, Jalan Sultan Hasanudin, number 43, Sawerigading, Ujung Pandang District, Makassar City, South Sulawesi. The main objective of this research is to find out the initial results before being given training and after being given training (technical guidance) on ways to answer questions about the Joint Selection for State Higher Education Entrance (SBMPTN). The method used in this research is the comparative method. The results of the trial before the training and after the training showed a significant difference. In other words, teachers can get pretty good grades after being guided, fostered, and specifically tested in training activities designed by the organizing committee for technical guidance to strengthen the competence of teachers in computer-based written exams.